Pengaruh Good Corporate Governance, Kinerja Keuangan, dan Earning Per Share terhadap Nilai Perusahaan Badan Usaha Milik Negara - Anggun Fitrah Sari; Ade Widiyanti; Ratna Septiyanti; Sari Indah Oktanti (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
The purpose of this study is to examine the effect of Good Corporate Governance (GCG), financial performance, and Earning Per Share (EPS) on firm value. The object of this research consists of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the period of 2021–2024. This study employs a quantitative approach using secondary data in the form of annual financial statements as the primary source. The sample was selected using purposive sampling based on predetermined criteria, ensuring that only companies with complete data and consistent reporting were included in the analysis. The independent variables analyzed include the audit committee, independent commissioners, institutional ownership, Return on Assets (ROA), and Earning Per Share (EPS). Multiple linear regression analysis was used to process the data in this study, allowing the researchers to examine the simultaneous and partial effects of the variables on firm value. The findings indicate that firm value is significantly influenced by financial performance, particularly ROA, highlighting the importance of operational efficiency and profitability in enhancing shareholder wealth. While certain GCG variables such as institutional ownership showed positive influence, other elements like audit committees and independent commissioners produced mixed results, suggesting that governance mechanisms may have varying effects depending on organizational context. Meanwhile, EPS demonstrated inconsistent results in relation to firm value, implying that market perceptions of earnings may not fully capture the impact on overall firm valuation. This study provides insights for policymakers, investors, and corporate managers on the relative importance of governance and financial indicators in value creation for state-owned enterprises.